Late onset anorexia nervosa treated with olanzapine : a case report - Santonastaso, Paolo (Array, 2008)
Summary: A case of late onset anorexia nervosa (AN) treated with olanzapine is reported. The patient suffered AN onset at the age of 53 and was brought to our attention four years later in a very poor state of health due to extreme starvation and laxative abuse. She presented severe obsessions about food, a very disturbed body image, and “ascetic” rituals of self-punishment. There was no improvement of her symptoms with cognitive behavioural therapy, antidepressant drugs and inpatient nutritional therapy. After the prescription of olanzapine, the patient was more cooperative and able to maintain a stable acceptable weight, although her psychiatric and anorexic symptoms only improved partially